The encoded and expressed biosynthetic potential of Greenland Ice Sheet microbes - Jaarsma, Ate H.; Sipes, Katie; Zervas, Athanasios; Feord, Helen K.; Campuzano Jiménez, Francisco; Thøgersen, Mariane S.; Benning, Liane G.; Tranter, Martyn; Anesio, Alexandre M. (Frontiers in Microbiology, 2025)
Supraglacial habitats of the Greenland Ice Sheet (GrIS) harbor active microbial communities. Microbes produce a plethora of natural products, which hold great promise in biotechnology. Understudied environments such as the Greenland Ice Sheet are therefore of interest for the discovery of unknown biosynthetic gene clusters (BGCs) that encode these compounds. Though many applications of these natural products have been identified, little is known about their ecological function for the producer itself. Some hints exist toward roles in competition and environmental adaptation, yet confirmation of the expression of these BGCs in the natural environment is often lacking. Here, we investigated the expression of BGCs in supraglacial habitats of the GrIS. Using total RNA sequencing, we conducted a seasonal study to analyze metatranscriptomes of ice and cryoconite habitats over a 21-day period during the ablation season. Genome mining on metagenomic contigs identified BGCs within ice and cryoconite metagenomes, after which the metatranscriptomes were mapped to them. Our study identified a majority of previously unknown BGCs, 59% of which are actively expressed in situ, with relatively stable expression levels throughout the melting season. The 10 most highly expressed BGCs in ice were of eukaryotic origin, whereas in cryoconite, the 10 most highly expressed BGCs were prokaryote-derived. Among these was biosynthetic machinery for the production of carotenoids, terpenes, beta-lactones, and modified peptides, and their producers are likely ecosystem engineers of the supraglacial habitats, such as glacier ice or snow algae, and cyanobacteria. These findings highlight the significant, yet mostly unexplored, biosynthetic capabilities of GrIS supraglacial microbes, and suggest an active role of these BGCs in community ecology.